Considerations for improving diversity, equity and inclusivity within research designs and teams. (January 2022) - Asmal, Laila; Lamp, Gemma; Tan, Eric J.
Highlights: Diversity, equity and inclusivity (DEI) in research teams increases innovation. Unconscious biases limit the success of researchers and teams. Insufficient DEI in research design limits generalisability of findings. To optimize DEI, transformation is needed at senior levels in the research process. Abstract: This article addresses the growing movement towards greater diversity, equity and inclusivity (DEI) within the research community. We present the case for increasing DEI among research teams and participants, discussing the benefits of this, as well as some of the current hindrances to achieving better DEI, particularly implicit biases. Lastly, we present some interventions that can be implemented within four key aspects of the research process: research methods, the research team, funding access and scientific dissemination. It is contingent on all players to engage in efforts to improve DEI in research settings, as they each are a critical step to improving the scientific method, rigor and accuracy of research outcomes.